1997
DOI: 10.1172/jci119490
|View full text |Cite
|
Sign up to set email alerts
|

The role of transglutaminase in the rat subtotal nephrectomy model of renal fibrosis.

Abstract: Tissue transglutaminase is a calcium-dependent enzyme that catalyzes the cross-linking of polypeptide chains, including those of extracellular matrix (ECM) proteins, through the formation of ⑀ -( ␥ -glutamyl) lysine bonds. This crosslinking leads to the formation of protein polymers that are highly resistant to degradation. As a consequence, the enzyme has been implicated in the deposition of ECM protein in fibrotic diseases such as pulmonary fibrosis and atherosclerosis.In this study, we have investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
142
0
5

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(157 citation statements)
references
References 46 publications
10
142
0
5
Order By: Relevance
“…However, previous studies have reported increased tTg levels accompanying externalization (Johnson et al, 1997 rather than just the redistribution of enzyme observed in the tubulointerstitium, an observation comparable to one we find in the glomerulus. It remains a possibility that the increased presence of tTg in the ECM and the ability of the enzyme to crosslink itself into the ECM, making it a difficult protein to extract, may explain the marginally lower levels of detectable enzyme in the diabetic kidney.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…However, previous studies have reported increased tTg levels accompanying externalization (Johnson et al, 1997 rather than just the redistribution of enzyme observed in the tubulointerstitium, an observation comparable to one we find in the glomerulus. It remains a possibility that the increased presence of tTg in the ECM and the ability of the enzyme to crosslink itself into the ECM, making it a difficult protein to extract, may explain the marginally lower levels of detectable enzyme in the diabetic kidney.…”
Section: Discussionsupporting
confidence: 90%
“…In common with our previous studies in the subtotal nephrectomy model of renal scarring (Johnson et al, 1997, there is an increase in tTg crosslink product within diabetic kidneys that potentially has significant biochemical effects on ECM regulation and turnover, either directly or via TGF-␤1 activation (Nunes et al, 1997). It is quite conceivable that tTg can cause excess deposition of ECM components because it has been shown in vitro to cause fibril formation in the absence of lysyl oxidase (Kleman et al, 1995;Johnson et al, 1999), and when overexpressed in fibroblasts causes increased deposition of fibronectin and latent TGF-␤1 (Verderio et al, 1999).…”
Section: Skill Et Alsupporting
confidence: 85%
See 3 more Smart Citations